Experimental determination of the "collimator monitoring fill factor" and its relation to the error detection capabilities of various 2D‐arrays. Issue 4 (18th February 2019) - Stelljes, Tenzin Sonam; Poppinga, Daniela; Kretschmer, Jana; Brodbek, Leonie; Looe, Hui Khee; Poppe, Björn
Abstract : Purpose: The collimator monitoring fill factor (CM‐FF) introduced by Stelljes et al. (2017) and the FWHM fill factor (FWHM‐FF) introduced by Gago‐Arias et al. (2012) were determined using the measured photon fluence response functions of various 2D‐arrays. The error detection capabilities of 2D‐arrays were studied by comparing detector signal changes and local gamma index passing rates in different field setups with introduced collimation errors. Methods: The fill factor is defined as the ratio of the sensitive detector area and the cell area of a detector, defined by the detector arrangement on a 2D‐array. Gago‐Arias et al. calculated the FWHM‐FF, using the FWHM ² of a detector's fluence response function K M ( x ) as the sensitive detector area. For the CM‐FF a sensitive detector width w(Δ mm, d%) is calculated. The sensitive detector width is the lateral extent of K M ( x ), lying inside the detector cell area, along which a collimator error of Δ mm yields a signal change exceeding a detection threshold of d %. The sensitive area for a single detector is calculated using w(Δ mm, d%) ². The CM‐FF is then calculated as the ratio of the sensitive area of a detector within its cell area and the detector cell area. The fluence response functions of the central detector of the OCTAVIUS 729, 1500, and 1000 SRS array (all PTW‐Freiburg, Freiburg, Germany) and the MapCHECK 2 array (Sun Nuclear, Melbourne, US) were measured using a photon slit beam. The FWHM‐FF and the CM‐FF were calculated and compared for all 2D‐arrays under investigation. The error detection capabilities of 2D‐arrays in quadratic fields were studied by investigating the signal changes in the detectors adjacent to the collimator edge when changing the collimator position. The change in local gamma index passing rate with respect to the introduced collimator error was investigated for an ionization chamber and a diode array in quadratic and two intensity modulated fields. Results: Values for the CM‐FF and FWHM‐FF were 1.0 and 0.35, respectively for the area of the liquid‐filled 1000 SRS ionization chamber array with a detector to detector distance of 5 mm and 0.32 and 0.04, respectively, for the MapCHECK 2 diode array. For the vented ionization chamber array OCTAVIUS 729 fill factors were calculated as CM‐FF = 0.59 and FWHM‐FF = 0.53, while the OCTAVIUS 1500 array yielded fill factors of CM‐FF = 0.77 and FWHM‐FF = 0.72. Signal changes in vented ionization chambers for collimator errors of 1 mm surpassed those of diodes by a factor of 2 in quadratic fields. The gamma index passing rates in quadratic fields reflect those findings. In intensity modulated fields, the decline of the gamma index passing rate is bigger for the ionization chamber array compared to the diode array when introducing collimator errors. Conclusions: The calculated values of the CM‐FF correlate with the signal changes in quadratic field setups with introduced collimator position errors of 1 mm, while the FWHM‐FF underestimates the error detection capabilities of 2D‐arrays. An increased error detection capability of the ionization chamber array compared to diode array was observed in quadratic and intensity modulated fields.